KUANTITAS DAN DISTRIBUSI JALUR PEJALAN KAKI DI KAWASAN CAMPURAN ZAINAL ABIDIN PAGAR ALAM, KOTA BANDAR LAMPUNG - Anggi Sijabat; Adinda Sekar Tanjung (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
A mixed area is one area that requires pedestrian path due to the commercial and non-commercial functions that are close to each other. Traveling short distances on foot will be more effective than using a vehicle because it is impossible to always stop at the desired location. One of the mixed-use areas with high mobility in Bandar Lampung is the Zainal Abidin Pagar Alam Mixed Area, Bandar Lampung City. The Zainal Abidin Pagar Alam Mixed Area does not meet the standards in fulfilling pedestrian path facilities. This is indicated by the fact that there are still many roads in this area with no pedestrian path. The condition compels pedestrian to pass through the road, thus increasing the risk of accidents. This study aims to identify the need and availability of pedestrian path in the Zainal Abidin Pagar Alam Mixed Area, based on pedestrian path' quantity, and distribution. This research employs a quantitative deductive method by placing theoretical analysis as the determination of the variable, and the population of this region using a census, namely all road corridors in the Region A mixture of Zainal Abidin Pagar Alam The results show that the quantity, and distribution, have not met the availability of pedestrian path based on PUPR Guidelines Standard No. 02 of 2018 on pedestrian Facility Planning.